Design and optimization of low speed horizontal-axis wind turbine using OpenFOAM - Hendriana, D. (Asian Research Publishing Network, 2015)
This paper presents a design and optimization of 7.5 m diameter, 6-bladed horizontal-axis wind turbine designed for low speed wind of 4 m/s; using opens source Computational Fluid Dynamics (CFD) software OpenFOAM. The blade configuration was chosen to be as simple as possible such that manufacturing cost can be reduced. In the simulations, a solver called simpleFoam based on the Reynolds Averaged Navier-Stokes (RANS) with k-Ï turbulence model and steadystate solution method is used. For validating both drag and torque calculations, three different validation cases were carried out and compared to popularly known experimental results. This validation study shows that by utilizing fine mesh resolutions the numerical errors associated with CFD solutions could be minimized to merely 2-4 compared to the experimental results. Optimization study was then conducted by varying the width of the blade, inclination angle of the outer tip of the blade, and inclination angle of the inner tip of the blade. This optimization yields power efficiency between 38-41. After a series of geometry fine tunings, the best modification was found at 52 power efficiency. It was found that variation of wind speed had little effect to the power efficiency but it varied the maximum power. On the other hand, the wind angle to wind turbine axis contributes very strong impact to the power efficiency. Â© 2006-2015 Asian Research Publishing Network (ARPN).